Effect of negative bias voltage on preparation of diamond-like carbon films with high interfacial strength - ZHENG Jinhua; LI Zhixiong; LIU Qingyun; MEI Shiyang (Cailiao gongcheng, 2023)
In order to solve the problem of interfacial bonding strength and thick film between diamond-like carbon(DLC) film and metal substrate, a new process using a-Si: C: H bonding layer and H-DLC transition layer was proposed. The composite DLC films under different negative bias voltage conditions were deposited on the 45 steel substrate by using DC plasma enhanced chemical vapor deposition (DC-PECVD) method, and the thickness, surface roughness, structural composition, residual stress, film-substrate adhesion and tribological properties of the films were measured and analyzed. The results show that when the negative bias voltage of the top layer film increases from 600 V to 1200 V, the surface roughness of the film increases, and the total film thickness increases to a maximum of 16.3 μm. The residual stress in the film tends to increase and the adhesion force decreases. The average wear rate of the film increases, and the wear resistance gradually decreases. When the negative bias voltage of the top film is 600 V, the composite DLC film has the best comprehensive performance, the bonding force reaches 54.6 N, the average wear rate is 1.5×10-16 m3/(N·m), and the wear resistance of 45 steel is improved by 30 times.